Dampak Kepemimpinan Transformasional dan Motivasi Kerja Terhadap Kinerja Karyawan - Deflin T. Nanulaitta; Carla C. Tousalwa; Leonora Ferdinandus (Journal of Business Application, 2022)
The purpose of this study was to analyze the impact of transformational leadership and work motivation on the performance of city management and engineering employees at PT. Ciputra International Citraland Bay View City Ambon. This type of research is explanatory research with a population of all employees of PT. Ciputra International Citraland Bay View City Ambon. Withdrawal of samples using cluster sampling technique, namely only employees of the city management section and engineering section with the final sample size of 78 respondents. Analysis of research data using Multiple Linear Regression Analysis. The results showed that transformational leadership and work motivation proved to have a positive and significant impact on the performance of city management and engineering employees at PT. Ciputra International Citraland Bay View City Ambon.